Porous ceramic laminate and separation membrane

JP2025022447APending Publication Date: 2025-02-14SUMITOMO CHEM CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023127030
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-03
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、積層界面での剥離が抑制された多孔質セラミックス積層体を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025022447000001_ABST
    Figure 2025022447000001_ABST
Patent Text Reader

Abstract

To provide a porous ceramic laminate in which two or more layers are laminated and peeling at a lamination interface is suppressed.SOLUTION: There is provided a porous ceramic laminate in which a layer containing small particles having a circle-equivalent particle diameter of less than 1 μm in a cross-section parallel to the lamination direction of the laminate is laminated on a first porous ceramic layer and the small particles and large particles having a circle-equivalent particle diameter of 2 to 25 μm are present on the surface of the first porous ceramic layer.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a porous ceramic laminate and a separation membrane. [Background technology]

[0002] Porous ceramic bodies are used in various fields as membranes having functions such as separation, concentration, or filtration of fluids, such as gases or liquids, such as microfiltration membranes, ultrafiltration membranes, nanofiltration membranes, reverse osmosis membranes, ion exchange membranes, and gas separation membranes.

[0003] It is important that porous ceramic bodies suitable for use in the fields described above can fully perform functions such as separation while allowing fluids to flow easily through the porous ceramic body. For this reason, they are usually composed of a laminate of two or more layers including a functional layer with a small pore diameter and a support layer with a large pore diameter that supports the functional layer.

[0004] For example, Patent Document 1 discloses a filter element comprising a porous hard support layer made of sintered mineral particles and having relatively large pores with diameters of about several microns to several tens of microns, and an additional porous layer provided on the support layer, the porous layer being composed of a first coating layer made of sintered mineral particles having a diameter almost equal to the pore diameter of the support layer, and a second coating layer made of sintered mineral particles having a diameter smaller than the pore diameter of the support layer, the first coating layer and the second coating layer being fixed to the support layer in this order by a sintering method, and the material of the additional porous layer being present on the support without substantially penetrating into the pores of the support layer. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 59-48646 Summary of the Invention [Problem to be solved by the invention]

[0006] In a laminate in which two or more types of layers are laminated, if the bonding at the interface of the layers is not strong when a load is applied to the laminate, peeling will occur at the interface of the layers.

[0007] The aforementioned Patent Document 1 also discloses a laminate as a structure of a separation membrane, but does not consider peeling at the lamination interface. Therefore, an object of the present invention is to provide a porous ceramic laminate in which two or more types of layers are laminated, in which peeling at the lamination interface is suppressed. [Means for solving the problem]

[0008] The present invention which achieves the above object is as follows. [1] A porous ceramic laminate, A porous ceramic laminate, characterized in that a first porous ceramic layer is laminated with a layer containing small particles having a circle-equivalent particle diameter of less than 1 μm in a cross section parallel to the lamination direction of the laminate, and the small particles and large particles having a circle-equivalent particle diameter of 2 to 25 μm are present on the surface of the first porous ceramic layer. [2] The average circle-equivalent particle diameter of the large particles is equal to or smaller than the average pore diameter D of the first porous ceramic layer. 50 The laminate according to [1], wherein the thickness is 0.3 times or more. [3] The laminate according to [1] or [2], in which, when observed on a cross section parallel to the stacking direction of the laminate, the proportion of small particles present on the surface of the first porous ceramic layer, represented by the ratio of L2 to L1 below: L2 / L1, is 10% or more. L1: the length within the observation field of view of a straight line X1 that contacts the first porous ceramic layer at two or more points and does not cross the first porous ceramic layer L2: The total length of the portion of the first porous ceramic layer where small particles are present on the surface of the first porous ceramic layer within the observation field along the surface. [4] The laminate according to any one of [1] to [3], wherein, when observed on a cross section parallel to the lamination direction of the laminate, the area ratio of the large particles in a portion sandwiched between the following lines X1 and X0 is 4% or more. Line X1: A line that contacts the first porous ceramic layer at two or more points and does not cross the first porous ceramic layer. Straight line X0: A line parallel to the straight line X1 and spaced 10 μm apart in the direction toward the inside of the first porous ceramic layer [5] The laminate according to any one of [1] to [4], wherein the layer containing the small particles comprises an outer layer containing the small particles but not the large particles, and an intermediate layer containing both the small particles and the large particles. [6] The laminate according to [5], wherein, when observed on a cross section parallel to the lamination direction of the laminate, the area ratio of the large particles in a portion sandwiched between the following lines X1 and X2 is 1 to 60%. Line X1: A line that contacts the first porous ceramic layer at two or more points and does not cross the first porous ceramic layer. Straight line X2: A parallel line 10 μm apart from the straight line X1 toward the outermost surface of the layer containing small particles from the surface of the first porous ceramic layer. [7] The laminate according to [5] or [6], further comprising another layer laminated between the intermediate layer and the outer layer or on top of the outer layer. [8] The laminate according to any one of [1] to [7], wherein the large particles and the small particles are made of an inorganic oxide. [9] The laminate according to any one of claims [1] to [8], which is in a tubular or monolithic shape.

[10] A separation membrane comprising the laminate according to any one of [1] to [9]. Effect of the Invention

[0009] According to the present invention, it is possible to provide a porous ceramic laminate in which peeling at the lamination interface is suppressed. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a set of photographs substituting for a drawing, illustrating a procedure for measuring the proportion of small particles present on the surface of the first porous ceramic layer. [Diagram 2] FIG. 2 is a photograph, substituted for a drawing, showing an SEM image of a cross section of the laminate obtained in Example 2. [Diagram 3] Figure 3(a) is a photograph showing the surface of the first porous ceramic layer used in the embodiment, observed by SEM; Figure 3(b) is a photograph showing the surface of the laminate obtained in Example 2, observed by SEM; and Figure 3(c) is a photograph showing the surface of the sample obtained in Comparative Example 1, observed by SEM. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The porous ceramic laminate of the present invention is a porous ceramic laminate in which a first porous ceramic layer is laminated with a layer containing small particles having a circle-equivalent particle diameter of less than 1 μm in a cross section parallel to the lamination direction of the laminate, and the small particles and large particles having a circle-equivalent particle diameter of 2 to 25 μm are present on the surface of the first porous ceramic layer (the surface on the side of the layer containing the small particles).

[0012] As described above, in order to reduce the pressure loss of the fluid flowing through the porous ceramic body while fully exerting the function of separation, concentration, or filtration, a functional layer having a pore diameter smaller than that of the support layer is usually laminated on a support layer having a large pore diameter. However, if a layer made of particles with a large particle diameter is directly laminated on the support layer, the bonding strength of the interface becomes insufficient. On the other hand, as shown in the comparative example described later, if a layer made of particles with a small particle diameter is to be laminated on the support layer, the small particles will enter the pores of the support layer, and the layer cannot be formed. In the porous ceramic laminate of the present invention, a layer containing small particles is formed on the surface of the first porous ceramic layer that becomes the support layer, and since small particles and large particles are present on the surface of the first porous ceramic layer, a layer can be formed on the support layer and the bonding strength of the interface can be improved.

[0013] The shape of the first porous ceramic layer is not particularly limited, and may be, for example, a plate shape, a tube shape, or a monolith shape, and is particularly preferably a tube shape or a monolith shape. In any of the above shapes, the corners may be rounded. The monolith shape means a columnar (cylinder, square column, elliptical column, etc.) shape having a plurality of holes (preferably a cylindrical shape) penetrating in the axial direction. When the first porous ceramic layer is tubular, the layer containing small particles is preferably formed on the inner circumferential surface of the tube. When the first porous ceramic layer is monolithic, the layer containing small particles is preferably formed on the inner circumferential surface of each through hole of the monolithic shape.

[0014] The porous ceramic laminate of the present invention has a layer containing small particles laminated on a first porous ceramic layer, and has the same shape as the first porous ceramic layer.

[0015] The thickness (average value) of the first porous ceramic layer is preferably 400 to 8000 μm. When the first porous ceramic layer is monolithic, the thickness may be the average value of the closest distance between adjacent tubes on a plane perpendicular to the long axis. The axial length of the first porous ceramic layer is, for example, 50 to 5000 mm, preferably 500 to 3000 mm. When the first porous ceramic layer is tubular, the outer diameter of the first porous ceramic layer is, for example, 5 mm to 20 mm, and the inner diameter of the tube is, for example, 1 mm to 15 mm. When the first porous ceramic layer is monolithic, i.e., when it has two or more tubes, the outer diameter of the first porous ceramic layer is, for example, 5 mm to 100 mm, and the inner diameter of each tube is, for example, 0.1 mm to 10 mm.

[0016] The first porous ceramic layer preferably contains an inorganic oxide, for example Li 2 O, BeO, B 2 O 3 , Na 2 O, MgO, Al 2 O 3 , SiO 2 , K 2O, CaO, ScO 2 , TiO 2 , V 2 O 5 , Cr 2 O 3 , ZnO, Ga 2 O 3 , GeO 2 , As 2 O 5 , Rb 2 O, SrO, Y 2 O 3 , ZrO 2 , Nb 2 O 5 , Ag 2 O, CdO, In 2 O 3 , SnO 2 , Sb 2 O 5 , TeO 2 , Cs 2 O, BaO, La 2 O 3 , Ta 2 O 5 , WO 3 , HgO, Tl 2 O, PbO, PbO 2 , and ThO 2 It is more preferable that the first porous ceramic layer contains at least one metal oxide selected from the group consisting of Al. 2 O 3 And, Al 2 O 3 It is more preferable that the first porous ceramic layer contains one or more metal oxides other than Al. 2 O 3 The one or more metal oxides other than the above can be arbitrarily selected from the metal oxides exemplified above, and the first porous ceramic layer is Al 2 O 3 and SiO 2 It is particularly preferable that the glass contains the metal. In this specification, the term "metal" is used to include semimetals such as Si.

[0017] The average pore diameter D of the first porous ceramic layer measured by mercury intrusion porosimetry 50is preferably 0.1 μm or more, more preferably 1 μm or more, and even more preferably 5 μm or more, and is preferably 20 μm or less, more preferably 18 μm or less, and even more preferably 15 μm or less. The pore diameter means the pore diameter showing a peak in a graph with the horizontal axis representing the pore diameter and the vertical axis representing the log differential pore volume.

[0018] In the present invention, the laminate is observed at a cross section parallel to the lamination direction of the laminate, and particles having a circle-equivalent particle diameter of less than 1 μm at the cross section are defined as small particles. The lower limit of the circle-equivalent particle diameter of the small particles may be about 0.05 μm. Meanwhile, particles having a circle-equivalent particle diameter of 2 μm to 25 μm at the cross section are defined as large particles. The cross section parallel to the lamination direction of the laminate can be, for example, a cross section perpendicular to the longitudinal direction of the laminate (for example, the axial direction when the laminate is cylindrical).

[0019] In the present invention, it is also preferable to adjust the ratio of large particles to small particles on the surface of the first porous ceramic layer. When observing a cross section parallel to the lamination direction of the laminate, the ratio of small particles present on the surface of the first porous ceramic layer, represented by the ratio of L2 to L1 below: L2 / L1, is preferably 10% or more. By making the ratio of small particles a predetermined value or more, the bonding strength between the first porous ceramic layer and the layer thereon can be improved. L1: the length within the observation field of view of a straight line X1 that contacts the first porous ceramic layer at two or more points and does not cross the first porous ceramic layer L2: The total length of the portion of the first porous ceramic layer where small particles are present on the surface of the first porous ceramic layer within the observation field along the surface.

[0020] Figure 1 shows the procedure for measuring the proportion of small particles on the surface of the first porous ceramic layer. As shown in Figure 1(a), a straight line X1 (symbol 11a) is drawn that contacts the first porous ceramic layer at two or more points but does not cross the first porous ceramic layer, and the length L1 of the straight line X1 within the observation field is measured. Next, as shown in Figure 1(b), the portions 11b and 12b on the surface of the first porous ceramic layer where small particles exist are identified, and their total length L2 is measured to calculate L2 / L1.

[0021] When there are multiple straight lines X1 in the observation field, the shortest straight line is adopted as X1. In addition, in a rectangular observation field with the lamination direction being the up-down direction of the paper, even if a straight line touches the first porous ceramic layer at two or more points, a straight line that does not intersect with the right and left ends of the observation field is not adopted as the straight line X1. The range of the observation field is set to a magnification of 1000 times when measuring the SEM photograph.

[0022] L2 / L1 is more preferably 15% or more, even more preferably 20% or more, even more preferably 25% or more, particularly preferably 30% or more, and most preferably 40% or more, and the upper limit may be, for example, 85%.

[0023] In addition, when observing a cross section parallel to the stacking direction of the laminate, it is preferable that the proportion of large particles on the surface of the first porous ceramic layer, evaluated by the area proportion of the large particles in the portion sandwiched between the lines X1 and X0 below, is 4% or more. Line X1: A line that contacts the first porous ceramic layer at two or more points and does not cross the first porous ceramic layer. Straight line X0: A line parallel to the straight line X1 and spaced 10 μm apart in the direction toward the inside of the first porous ceramic layer

[0024] The area ratio of the large particles is 4% or more, more preferably 10% or more, further preferably 15% or more, and particularly preferably 22% or more, and the upper limit may be, for example, 35%.

[0025] In the present invention, it is preferable that the surface of the first porous ceramic layer does not contain particles having a circle-equivalent particle diameter exceeding 25 μm as much as possible. Specifically, the area ratio of particles having a circle-equivalent particle diameter exceeding 25 μm in the part sandwiched between the lines X1 and X0 in the observation field of view is preferably 2% or less, more preferably 1% or less, and even more preferably 0%.

[0026] The large particles (having a circle-equivalent particle diameter of 2 to 25 μm) present on the surface of the first porous ceramic layer have an average circle-equivalent particle diameter that is smaller than the average pore diameter D of the first porous ceramic layer. 50 The average diameter of the large particles is preferably 0.3 times or more, more preferably 0.6 times or more, and by doing so, it is preferable that the large particles are not taken into the pores of the first porous ceramic layer which serves as the support layer. 50 It is preferable that the average circle-equivalent particle diameter of the large particles present on the surface of the first porous ceramic layer is 2.8 times or less. The average circle-equivalent particle diameter of the large particles present on the surface of the first porous ceramic layer can be determined by arbitrarily selecting 20 large particles in the portion between the lines X1 and X0 and calculating the average circle-equivalent particle diameter of the large particles. Note that the large particles in the portion between the lines X1 and X0 below refer to particles in which at least a part is present in the portion between the lines X1 and X0, and if the target large particle has a portion protruding from the lines X1 and X0, the circle-equivalent particle diameter of the entire large particle including the protruding portion is measured.

[0027] In the porous ceramic laminate of the present invention, a layer containing small particles is laminated on the first porous ceramic layer, and the layer containing small particles is preferably composed of an outer layer containing the small particles and not the large particles, and an intermediate layer containing both the small particles and the large particles. The thickness of the intermediate layer can be, for example, 3 to 100 μm, and is preferably 3 to 60 μm. The thickness of the outer layer is, for example, 5 to 100 μm, and more preferably 20 to 80 μm.

[0028] For the intermediate layer, in a cross section parallel to the stacking direction of the laminate, straight lines are drawn from any three or more points on the surface of the first porous layer (the surface on the intermediate layer side) in the stacking direction (for example, the thickness direction if the laminate is in the form of a plate, or the radial direction of the through hole if the laminate is in the form of a tube or monolith having a cylindrical through hole and the intermediate layer is formed on the inner surface of the through hole), and the length of the line segments to the point where they intersect with the interface between the intermediate layer and the outer layer is measured, and the average value of the three or more line segments can be regarded as the thickness of the intermediate layer. For the outer layer, straight lines can be drawn in the stacking direction from any three or more points on the interface between the intermediate layer and the outer layer, and the length of the line segments to the points where they intersect with the surface of the outer layer can be measured, and the average value of the three or more line segments can be the thickness of the outer layer.

[0029] When the layer containing small particles includes an intermediate layer and an outer layer, the ratio of large particles in the intermediate layer evaluated by the area ratio of the large particles in the portion sandwiched between the above-mentioned line X1 and the below-mentioned line X2 when observing a cross section parallel to the lamination direction of the laminate is preferably 1 to 60%. Straight line X2: A parallel line 10 μm apart from the straight line X1 toward the outermost surface of the layer containing small particles from the surface of the first porous ceramic layer.

[0030] The proportion of large particles in the intermediate layer is 5% or more, more preferably 10% or more, further preferably 25% or more, and particularly preferably 35% or more, with the upper limit being, for example, 90% or 80%.

[0031] Furthermore, when the layer containing small particles includes an intermediate layer and an outer layer, another layer may be laminated between the intermediate layer and the outer layer, or on the outer layer.

[0032] The large particles and the small particles are preferably inorganic oxides. In a preferred embodiment, the above-mentioned examples of the metal oxides contained in the first porous ceramic layer can be referred to. In particular, both the large particles and the small particles are Al. 2 O 3 It is preferable that Al 2 O 3As the alumina, commercially available α-alumina can be used without any particular limitation, but as large particles, AA-10, AA-5, etc., manufactured by Sumitomo Chemical Co., Ltd. can be used, and as small particles, AKP-3000, AKP-20, etc., manufactured by Sumitomo Chemical Co., Ltd. can be used.

[0033] The method for producing the porous ceramic laminate of the present invention is not particularly limited, and the porous ceramic laminate may be produced by applying a slurry containing particles X1 having a volume-based cumulative 50% equivalent diameter of 1 to 20 μm and particles X2 having a volume-based cumulative 50% equivalent diameter of 0.05 μm or more and less than 1 μm onto the first porous ceramic layer by a dipping method, a spray coating method, a spin coating method, a bar coating method, or the like, and drying the slurry. Alternatively, the porous ceramic laminate may be produced by further applying a slurry containing particles Y1 having a volume-based cumulative 50% equivalent diameter of 0.05 μm or more and less than 1 μm, but not containing particles having a volume-based cumulative 50% equivalent diameter of 1 to 20 μm, after the drying, and drying the slurry.

[0034] Particles having a volume-based cumulative 50% equivalent diameter of 1 to 20 μm correspond to the above-mentioned large particles, and particles having a volume-based cumulative 50% equivalent diameter of 0.05 μm or more and less than 1 μm correspond to the above-mentioned small particles.

[0035] In particular, when the first porous ceramic layer is tubular or monolithic, the first porous ceramic layer may be produced by a method in which a slurry containing particles is formed on the inner surface of a tube or monolith using a jig (hereinafter, referred to as a ball injection method). This will be described in more detail below.

[0036] The ball injection method is a method for producing a ceramic porous laminate by forming a ceramic porous layer on the inner surface of a tubular or monolithic first porous ceramic layer, i.e., a first porous ceramic layer having one or more tubes (hereinafter sometimes referred to as a substrate), and is a production method comprising a slurry liquid supplying step (1) for supplying a slurry liquid containing particles to the inside of the tube, and a coating layer forming step (2) for passing a jig through the tube to form a coating layer of the slurry liquid on the inner surface of the tube while supplying the slurry liquid or after supplying the slurry liquid.

[0037] The slurry liquid containing particles is a raw material for the ceramic porous layer formed on the substrate. In a preferred embodiment of the ball injection method, a slurry liquid X supply step (1X) of supplying a slurry liquid X containing particles X1 having a cumulative 50% equivalent diameter on a volume basis of 1 to 20 μm to the inside of a substrate having one or more tubes, a coating layer forming step (2X) of the slurry liquid X, and a drying step (3X) are performed to form a coating layer containing particles X1 on the inner surface of the tube, and a slurry liquid Y supply step (1Y) of supplying a slurry liquid Y containing particles Y1 having a cumulative 50% equivalent diameter on a volume basis of 0.05 μm or more to less than 1 μm to the inside of the tube on which the coating layer containing particles X1 has been formed, a coating layer containing particles Y1 is formed by carrying out a coating layer forming step (2Y) of the slurry liquid Y, and a drying step (3Y). A heat treatment step (4X) may be further performed after the drying step (3X), or a heat treatment step (4Y) may be further performed after the drying step (3Y). It is also preferable that the slurry liquid X contains particles X2 having a volume-based cumulative 50% equivalent diameter of 0.05 μm or more and less than 1 μm together with the particles X1. The particles X1 having a volume-based cumulative 50% equivalent diameter of 1 to 20 μm correspond to the above-mentioned large particles, and the particles X2 and Y1 having a volume-based cumulative 50% equivalent diameter of 0.05 μm or more and less than 1 μm correspond to the above-mentioned small particles.

[0038] The slurry liquid preferably contains a dispersant, a thickener and a solvent in addition to the particles.

[0039] The dispersant can suppress the aggregation of inorganic particles in the slurry. The dispersant may be any of cationic surfactants, anionic surfactants, nonionic surfactants, and amphoteric surfactants. Among them, anionic surfactants such as polycarboxylate ammonium salts and polycarboxylate amine salts are preferred, and SN Dispersant 5020, SN Dispersant 5023, SN Dispersant 5027, SN Dispersant 5468, Noparfa D-6010, Nopcol 5200, Nopcosant RFA, Nopcosperse 6100, and Nopcosperse 6150 manufactured by San Nopco Co., Ltd. may be used. The concentration of the dispersant in the slurry (in terms of active ingredient) is preferably, for example, 0.01% by mass or more and 10% by mass or less with respect to 100% by mass of inorganic particles in the slurry.

[0040] Examples of the thickener include methyl cellulose, hydroxyethyl methyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, polyalkylene oxide, polyvinyl alcohol, sodium polyacrylate, polyvinylpyrrolidone, polyacrylamide, polydimethylaminoethyl methacrylate, etc., and hydroxypropyl methyl cellulose is particularly preferred. The amount of the thickener to be added can be appropriately adjusted depending on the target slurry viscosity.

[0041] The solvent may be water or an organic solvent.

[0042] When supplying the slurry liquid to the substrate and when passing the jig through the pipe, it is preferable to arrange the substrate so that the axial direction thereof is vertical.

[0043] In the slurry liquid supplying step (1), the slurry liquid may be supplied from either end of the substrate, but when the substrate is arranged so that its axial direction is vertical, it is preferable to supply the slurry liquid from the lower end of the substrate. The supply of the slurry liquid may be carried out by injecting the slurry liquid from the end of the substrate, or by masking the substrate end face other than the hole of the tube and the substrate side surface and immersing the substrate in the slurry liquid, but it is preferable to supply the slurry liquid by injection from the end of the substrate (particularly one end).

[0044] In the coating layer forming step (2) of the slurry liquid, by using a jig, the excess of the slurry liquid supplied to the inner tube surface of the substrate can be discharged, and the slurry liquid can be uniformly applied to the inner tube surface of the substrate. The jig may be passed through the tube after the slurry liquid is supplied, or may be passed through the tube while the slurry liquid is being supplied. It is preferable to supply the slurry liquid to the inside of the tube and pass the jig after the slurry liquid is supplied, and it is more preferable to supply the slurry liquid to the inside of the tube by injection and pass the jig after the slurry liquid is injected.

[0045] The direction of supply of the slurry liquid and the direction of passing the jig may be the same or different. When the substrate is arranged so that the axial direction is vertical, it is preferable to pass the jig from the upper end after the slurry liquid is supplied from the end of the substrate to the inner tube surface of the substrate.

[0046] The method of passing the jig through the tube of the substrate includes (i) flowing a fluid other than the slurry liquid from the rear of the jig in the direction of the jig's movement, (ii) sucking the slurry liquid from the direction of the jig's advancement, or (iii) performing both of these. In addition, when the substrate is arranged so that the axial direction is vertical, (iv) the jig may be passed through by dropping it from the upper end of the substrate under its own weight. The fluid includes a gas such as air. The method of moving the jig is particularly preferably (i) to (iii), and more preferably (i). In the embodiment (i), when a fluid other than the slurry liquid is flowed, the pressure of the fluid may be, for example, 0.01 MPa to 0.5 MPa.

[0047] After the jig is passed through the tube of the substrate, a fluid such as air may be passed through the tube to hold the tube in a pressurized state for a certain period of time, and in this way, the solvent, thickener, etc. in the slurry can be discharged to the outside of the tube through the pores of the substrate. The pressurizing pressure is, for example, 0.01 MPa to 0.5 MPa, and the holding time is, for example, 1 to 30 minutes.

[0048] The material of the jig is not particularly limited, and a jig made of resin, metal, ceramic, or the like can be used. The shape of the jig is preferably such that when projected in the moving direction of the jig inside the pipe, at least a part of the outer periphery of the projection is curved, specifically, a coil shape, a cylindrical shape, an elliptical cylindrical shape, a cone shape, a spherical shape, and a shape combining these shapes can be mentioned. In addition, among these shapes, a shape other than a coil shape is preferably cut with one or more planes parallel to the moving direction of the jig, and a part of the outer periphery is removed while leaving a part of it, and the jig may be moved inside the pipe while rotating. The shape of the jig is preferably such that the inner periphery shape of the cross section perpendicular to the axial direction of the pipe is a circle, specifically, a cylinder or a sphere, and a sphere is more preferable. The size of the jig may be appropriately adjusted according to the thickness of the ceramic porous layer to be formed within a range that can be inserted inside the pipe.

[0049] After forming a coating layer of the slurry liquid on the inner surface of the pipe using a jig, a drying step (3) is usually carried out to dry the coating. Drying is preferably performed by air-drying the coating layer, and the temperature of the air blown onto the coating may be room temperature or may be hot air in the range of 100° C. or less. The speed of the air blown onto the coating surface is, for example, 0.05 to 1 m / sec.

[0050] After the drying step (3), a heat treatment step (4) is preferably carried out. The heat treatment promotes sintering of particles (preferably inorganic oxides) contained in the slurry liquid, and can improve the strength of the layer formed from the slurry liquid and appropriately adjust the porosity. The heat treatment is preferably carried out at, for example, 300 to 1500°C. The heat treatment time is, for example, 30 minutes to 10 hours.

[0051] The thickness of the ceramic porous layer formed on the tube inner surface of the substrate may be adjusted by, for example, adjusting the viscosity of the slurry liquid; performing a series of steps including the slurry liquid supply step (1) and the slurry liquid coating layer formation step (2) (and, if necessary, the drying step (3) and the heat treatment step (4)) two or more times; adjusting the particle concentration in the slurry; or adjusting the size of the jig.

[0052] The ceramic porous laminate obtained by the present invention can be used as a microfiltration membrane, an ultrafiltration membrane, or a nanofiltration membrane, and, if necessary, by laminating a functional layer thereon, can be used as a microfiltration membrane, an ultrafiltration membrane, a nanofiltration membrane, a reverse osmosis membrane, an ion exchange membrane, a separation membrane for gases, etc.

[0053] Examples of the functional layer include zeolite, MOF (Metal Organic Frameworks), porous silica membrane, and porous alumina membrane. A separation membrane with a functional layer can be produced by applying a liquid containing inorganic particles or MOF that constitute the functional layer to the surface of the ceramic porous laminate obtained by the present invention and reacting it. The synthesis conditions can be appropriately selected depending on the functional layer to be laminated, and may be, for example, 80 to 800°C for 1 to 72 hours. EXAMPLES

[0054] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples, and can of course be modified within the scope of the above and below-mentioned aims, and all such modifications are within the technical scope of the present invention.

[0055] The examples and comparative examples described later were evaluated according to the following methods.

[0056] (1) Method for measuring pore diameter of substrate Substrate pore diameter D 50After drying the substrate at 120°C for 4 hours, the diameter was measured by mercury intrusion porosimetry using an Autopore IV9520 (Micromeritics). The mercury intrusion porosimetry produced a graph with the pore diameter on the horizontal axis and the cumulative log differential pore volume on the vertical axis, and the cumulative 50% equivalent diameter was obtained. The details of the measurement conditions are as follows. Adv. Contact Angle: 140.0° Rec. Contact Angle: 140.0° Mercury Temperature:21°C Sample Mass: 1.0g Assembly Mass: 1.0g Penetrometer Volume: 1.0mL Penetrometer Mass: 1.0g Report Range:1.07 to 59,256.30psia

[0057] (2) Method for measuring particle size of inorganic oxides The particle size distribution of the alumina used in the examples and comparative examples was measured using a laser diffraction / scattering particle size distribution measuring device (Microtrac MT3300EX II, 0.2 mass% aqueous solution of sodium hexametaphosphate, manufactured by Microtrac Corporation), and the volume-based cumulative 50% equivalent diameter was measured.

[0058] (3) Cross-sectional observation of laminate The cylindrical porous ceramic laminate obtained in the examples was cut in a cross section perpendicular to the axial direction, embedded in resin so that the cut surface could be observed, and mechanically polished. Platinum was vapor-deposited on the polished surface, and the cross section was observed and photographed at 1000x magnification using a FE-SEM (JSM-7500FA (manufactured by JEOL). The perimeter of the particles observed in the obtained SEM image was determined, and the particle was considered to be a circle with that perimeter, and the diameter of the particle was calculated to be the equivalent circle particle diameter of the particle. From the obtained equivalent circle particle diameter, the presence of large and small particles was confirmed. The equivalent circle particle diameter of the small particles was measured by enlarging it to a degree where the equivalent circle particle diameter could be confirmed (for example, 20,000x).

[0059] (4) Proportion of small particles on the surface of the first porous ceramic layer In the SEM image obtained in (3) above, the following lengths L1 and L2 were determined, and the ratio of L2 to L1: L2 / L1 was calculated. L1: the length within the observation field of view of a straight line X1 that contacts the first porous ceramic layer at two or more points and does not cross the first porous ceramic layer L2: The total length of the portion of the first porous ceramic layer where small particles are present on the surface of the first porous ceramic layer within the observation field along the surface.

[0060] (5) Area ratio of large particles on the surface of the first porous ceramic layer In the SEM image obtained in (3) above, the total area of ​​the large particles in the portion sandwiched between the lines X1 and X0 below was measured, and the total area was divided by the area of ​​the portion sandwiched between the lines X1 and X0 within the observation field of view to calculate the area ratio of the large particles on the surface of the first porous ceramic layer. Line X1: A line that contacts the first porous ceramic layer at two or more points and does not cross the first porous ceramic layer. Straight line X0: A line parallel to the straight line X1 and spaced 10 μm apart in the direction toward the inside of the first porous ceramic layer In addition, 20 large particles were arbitrarily selected from the portion between the lines X1 and X0, and the average value of the circle-equivalent particle diameters of the large particles was calculated.

[0061] (6) Area ratio of large particles in the intermediate layer In the SEM image obtained in (3) above, the total area of ​​the large particles in the portion sandwiched between the lines X1 and X2 below was measured, and divided by the area of ​​the portion sandwiched between the lines X1 and X2 within the observation field of view to calculate the area ratio of the large particles in the intermediate layer. Line X1: A line that contacts the first porous ceramic layer at two or more points and does not cross the first porous ceramic layer. Straight line X2: A parallel line 10 μm apart from the straight line X1 toward the outermost surface of the layer containing small particles from the surface of the first porous ceramic layer.

[0062] (7) Observation of the sample surface The surface of the first porous ceramic layer, the surface of the laminate obtained in Example 2 described below, and the surface of the sample obtained in Comparative Example 1 were each observed using a scanning electron microscope TM4000 manufactured by Hitachi High-Tech Corporation.

[0063] (8) Peel strength measurement The porous ceramic laminates obtained in the examples and comparative examples were evaluated according to JIS K5600 General Test Method for Paint Scratch Hardness (Pencil Method) 5-4. A pencil hardness tester (Yasuda Seiki Seisakusho Co., Ltd. 553-M1, weight: 750g, pencil moving speed: 1mm / sec) was used to draw a line on the laminate surface of the laminate with a soft pencil (Mitsubishi Pencil Co., Ltd.: Mitsubishi Uniseries 6B-9H), and the surface was observed using a digital microscope (Keyence Corporation: VHX-5000), and the hardness just before the hardness at which peeling, dents, or scratches were observed was evaluated as the hardness of the sample. Samples with hardness of 9H-H were evaluated as ◯, samples with hardness of F-HB were evaluated as △, and samples with hardness of B-6B were evaluated as ×.

[0064] Example 1 (First porous ceramic layer) The first porous ceramic layer is made of alumina and SiO 2 The alumina substrate CRM0107 (cylinder shape with inner diameter of 6.5 mm, outer diameter of 10.0 mm, length of 12.5 cm, average pore diameter D 50 The diameter was approximately 6.1 μm.

[0065] (Preparation of intermediate layer slurry) Alumina powders AA-5 (cumulative 50% equivalent diameter on a volume basis is approximately 6.6 μm) and AKP-3000 (cumulative 50% equivalent diameter on a volume basis is approximately 0.67 μm) manufactured by Sumitomo Chemical Co., Ltd., hydroxypropyl methylcellulose 60SH-4000 manufactured by Shin-Etsu Chemical Co., Ltd. as a thickener, and SN Dispersant 5468 (active ingredient 41%) as a dispersant were mixed with water at concentrations of 13.5 mass%, 1.5 mass%, 3.2 mass%, and 1.5 mass%, respectively, and the mixture was defoamed to prepare slurry S1.

[0066] (Formation of the intermediate layer) The slurry was filled into a catheter syringe manufactured by Terumo Corporation, and the syringe was left standing for 1 hour with the outlet facing downward. A tube was attached to the tip of the catheter syringe manufactured by Terumo Corporation, and the tip of the tube was connected to one end of the vertically placed substrate (hereinafter referred to as end A; the other end opposite end A is referred to as end B) with the end facing downward, and the slurry S1 was injected into the entire inside of the substrate.

[0067] After injecting the slurry S1, a ball with a diameter of 5.5 mm was set at the end B (upper end side) of the substrate, and the slurry S1 was discharged by flowing air from the end B at an air pressure of 0.1 MPa to move the ball from the end B to the end A, and after discharging the slurry S1, the ball was held at the end A and maintained at 0.1 MPa for 600 seconds. After 600 seconds, the substrate was rotated at 6.9 rpm while blowing hot air of about 0.1 m / s over the inner circumferential surface of the substrate to dry it, and a layer (intermediate layer) containing AA-5 particles and AKP-3000 particles was formed on the inner circumferential surface of the substrate.

[0068] (Preparation of Slurry for Outer Layer) Alumina powder AKP-3000 manufactured by Sumitomo Chemical Co., Ltd., a thickener hydroxypropyl methylcellulose 60SH-4000 manufactured by Shin-Etsu Chemical Co., Ltd., and a dispersant SN Dispersant 5468 were mixed in water at concentrations of 9.0 mass%, 3.2 mass%, and 0.9 mass%, respectively, and the mixture was defoamed to prepare slurry S2.

[0069] (Formation of outer layer 1) The slurry was filled into a catheter syringe manufactured by Terumo Corp., and the syringe was left standing for 1 hour with the outlet facing downward. A tube was attached to the tip of the catheter syringe manufactured by Terumo Corp., and the tip of the tube was connected to the end A of the substrate having a layer containing AA-5 particles and AKP-3000 particles formed on the inner surface thereof, which was placed vertically, with the end A facing downward, and the slurry S2 was injected into the entire inside of the substrate.

[0070] After injecting the slurry S2, a ball with a diameter of 5.5 mm was set at the end B of the substrate, and air was flowed from the end B at an air pressure of 0.02 MPa to move the ball from the end B to the end A, thereby discharging the slurry. The substrate was rotated at 6.9 rpm, and hot air of about 0.1 m / s was blown through the inner surface of the substrate to dry it, forming a layer containing AKP-3000 on the layer (intermediate layer) containing AA-5 particles and AKP-3000. The substrate having a layer containing AA-5 particles and AKP-3000 particles and a layer containing AKP-3000 formed on the inner surface was heat-treated at 1200 ° C. for 3 hours.

[0071] (Formation of outer layer 2) After the heat treatment, the same operation as in "Formation of outer layer 1" was carried out to obtain a porous ceramic laminate.

[0072] Example 2 A porous ceramic laminate of Example 2 was obtained in the same manner as in Example 1, except that the concentrations of the alumina powders AA-5 and AKP-3000 in the slurry S1 were set to 12.0 mass % and 3.0 mass %, respectively.

[0073] Example 3 A porous ceramic laminate of Example 3 was obtained in the same manner as in Example 1, except that the concentrations of the alumina powders AA-5 and AKP-3000 in the slurry S1 were set to 10.5% by mass and 4.5% by mass, respectively.

[0074] Example 4 A porous ceramic laminate of Example 4 was obtained in the same manner as in Example 1, except that the concentrations of the alumina powders AA-5 and AKP-3000 in the slurry S1 were set to 6.0 mass % and 9.0 mass %, respectively.

[0075] Example 5 A porous ceramic laminate of Example 5 was obtained in the same manner as in Example 1, except that the concentrations of the alumina powders AA-5 and AKP-3000 in the slurry S1 were set to 3.0 mass % and 12.0 mass %, respectively.

[0076] Comparative Example 1 As the first porous layer, the alumina base CRM0107 manufactured by Nanjing Tangent Fluid Technology Co., Ltd., the same as in Example 1, was used.

[0077] Alumina powder AKP-3000 manufactured by Sumitomo Chemical Co., Ltd., hydroxypropyl methylcellulose 60SH-4000 manufactured by Shin-Etsu Chemical Co., Ltd. as a thickener, and SN Dispersant 5468 as a dispersant were mixed in water at concentrations of 9.0 mass%, 3.2 mass%, and 0.9 mass%, respectively, and degassed to prepare a slurry. A catheter syringe manufactured by Terumo Corporation was filled with the slurry, and the syringe was left standing for 1 hour with the outlet facing downward.

[0078] A tube was attached to the tip of a catheter syringe manufactured by Terumo Corporation, and the tip of the tube was connected to one end A of the substrate placed vertically with the end A facing downward, and the slurry was injected into the entire inside of the substrate.

[0079] After injecting the slurry, a ball with a diameter of 5.0 mm was set at the end B opposite to the end A of the substrate, and the slurry was discharged by flowing air from end B at an air pressure of 0.1 MPa to move the ball from end B to end A. After discharging the slurry, the ball was held at end A and maintained at 0.1 MPa for 600 s. After 600 seconds, the substrate was rotated at 6.9 rpm while blowing hot air at about 0.1 m / s through the inner circle of the substrate to dry it, and an attempt was made to form a layer containing AKP-3000 particles on the inner surface of the substrate.

[0080] Fig. 2 shows an SEM image of the cross section of the laminate obtained in Example 2 according to (3) above. As shown in Fig. 2, in Example 2, a layer containing small particles 22 with a circle-equivalent particle diameter of less than 1 μm was laminated on the first porous ceramic layer 21, and it was confirmed that the small particles 22 and large particles 23 with a circle-equivalent particle diameter of 2 to 25 μm were present on the surface of the first porous ceramic layer 21, and a similar state was observed in the other Examples. Furthermore, in Examples 1 to 3, it was confirmed that an intermediate layer containing both small particles and large particles, and an outer layer containing small particles and not containing the large particles were formed on the first porous ceramic.

[0081] FIG. 3 shows the results of surface observation according to (7) above. FIG. 3(a) is the surface of the first porous ceramic layer, FIG. 3(b) is the surface of the laminate of Example 2, and FIG. 3(c) is the surface of the sample of Comparative Example 1. In FIG. 3(b), it can be seen that a layer different from the first porous ceramic layer shown in FIG. 3(a) has been formed, while in FIG. 3(c), it can be seen that the AKP-3000 particles have entered the pores of the first porous ceramic layer, and it can be seen that a layer different from the first porous ceramic layer has not been formed.

[0082] The results of measurements made according to the above (4), (5), (6) and (8) are shown in Table 1. In Table 1, the first porous ceramic layer is represented as the "first layer."

[0083] [Table 1]

[0084] In all of Examples 1 to 5, the average circle-equivalent particle diameter of the large particles in the portion sandwiched between the lines X1 and X0 was 4.5 μm.

[0085] For Examples 2 to 4 in which the outer layer and the intermediate layer were observed in the layer containing small particles, the cylindrical porous ceramic laminate was observed in a cross section perpendicular to the axial direction, and straight lines were drawn from any five points on the first porous layer surface (the surface on the intermediate layer side) in the lamination direction (diameter of the circle) to the point where the line segments intersect with the outer layer side surface of the AA-5 particles, and the average value of the five line segments was obtained as the thickness of the intermediate layer, which was about 18 μm in Example 2, about 22 μm in Example 3, and about 22 μm in Example 4. In addition, the cylindrical porous ceramic laminate was observed in a cross section perpendicular to the axial direction, and straight lines were drawn from any five points on the interface between the intermediate layer and the outer layer in the lamination direction (diameter of the circle), and the length of the line segments was measured to the point where the line segments intersect with the outer layer surface, and the average value of the five line segments was obtained as the thickness of the outer layer, which was about 61 μm in Example 2, about 56 μm in Example 3, and about 53 μm in Example 4.

Claims

1. A porous ceramic laminate, A porous ceramic laminate, characterized in that a layer containing small particles having a circle-equivalent particle diameter of less than 1 μm in a cross section parallel to the lamination direction of the laminate is laminated on a first porous ceramic layer, and the small particles and large particles having a circle-equivalent particle diameter of 2 to 25 μm are present on the surface of the first porous ceramic layer.

2. The average circle-equivalent particle diameter of the large particles is equal to or larger than the average pore diameter D of the first porous ceramic layer. 50 The laminate according to claim 1, wherein the thickness is 0.3 times or more.

3. The laminate described in claim 1, wherein, when observed at a cross section parallel to the stacking direction of the laminate, the proportion of small particles present on the surface of the first porous ceramic layer, represented by the ratio of L2 to L1 below: L2 / L1, is 10% or more. L1: the length within the observation field of view of a straight line X1 that contacts the first porous ceramic layer at two or more points and does not cross the first porous ceramic layer L2: The total length of the portion in which small particles are present on the surface of the first porous ceramic layer within the observation field along the surface

4. 2. The laminate according to claim 1, wherein, when observed on a cross section parallel to the lamination direction of the laminate, the area ratio of the large particles in a portion sandwiched between the following lines X1 and X0 is 4% or more. Line X1: A line that contacts the first porous ceramic layer at two or more points and does not cross the first porous ceramic layer. Line X0: A line parallel to the line X1 and spaced 10 μm apart in the direction toward the inside of the first porous ceramic layer.

5. 2. The laminate of claim 1, wherein the layer containing the small particles comprises an outer layer containing the small particles and not the large particles, and an intermediate layer containing both the small particles and the large particles.

6. 6. The laminate according to claim 5, wherein, when observed in a cross section parallel to the lamination direction of the laminate, the area ratio of the large particles in a portion sandwiched between the following lines X1 and X2 is 1 to 60%: Line X1: A line that contacts the first porous ceramic layer at two or more points and does not cross the first porous ceramic layer. Line X2: A line parallel to the line X1 and spaced 10 μm from the surface of the first porous ceramic layer toward the outermost surface of the layer containing small particles.

7. 6. The laminate according to claim 5, further comprising another layer laminated between the intermediate layer and the outer layer or on the outer layer.

8. 2. The laminate according to claim 1, wherein the large particles and the small particles are inorganic oxides.

9. 2. The laminate according to claim 1, which is in the form of a tube or a monolith.

10. A separation membrane comprising the laminate according to claim 1 .

Citation Information

Patent Citations

  • Semiconductor charge sensor

    JP1984048646A